Triggering Receptor Expressed on Myeloid Cells 2 Overexpression Inhibits Proinflammatory Cytokines in Lipopolysaccharide-Stimulated Microglia - Zhang, Xiaobao; Yan, Fang; Cui, Jizheng; Wu, Yong; Luan, Hengfei; Yin, Miaomiao; Zhao, Zhibin; Feng, Jiying; Zhang, Jinwei (Mediators of Inflammation, 2017)
Microglia play an important role in mediating inflammatory processes in the central nervous system (CNS). Triggering receptor expressed on myeloid cells 2 (TREM2) is a microglia-specific receptor and could decrease neuropathology in Alzheimer’s disease (AD). However, the detailed mechanism remains unclear. This study was designed to elucidate the effect of TREM2 on microglia. We showed that lipopolysaccharide (LPS) stimulation significantly increases proinflammatory cytokines and suppressed TREM2 in microglia. In addition, TREM2 overexpression inhibited LPS-induced microglia activation and elevated M2 phenotype of microglia. Together, our results demonstrate that TREM2 overexpression reduced LPS-induced proinflammatory cytokine release in microglia and increased M2 phenotype of microglia. These findings provide novel insights that the regulation of microglia polarization may be an approach for ameliorating microglia inflammation in neurodegenerative diseases.